Pengaruh Pemasaran Syariah Offline dan Online terhadap Loyalitas Pelanggan dalam Mengkonsumsi Produk Halal Bermerek Wardah - Sindi Nurfatikasari; Susilo, Edi (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
This study aims to determine the effectiveness of Offline Sharia Marketing and Online Sharia Marketing on Customer Loyalty in consuming Wardah branded halal products. Offline Sharia Marketing is introducing products indirectly with the media used such as newspapers, pamphlets, slayers and brochure brochures. On the other hand, online marketing uses digital technology to promote products or services that are targeted, iteractive and measurable. The main purpose of internet marketing was to promote products, increase referrals and increase traffic through various online marketing techniques. The data analysis method uses the Classical Assumption Test which is then carried out using SPSS 20. The research results indicate that both offline and online sharia marketing have a significant influence, whether individually or collectively, on Wardah customers' loyalty in consuming branded halal products. Marketing strategies based on sharia principles are considered effective in enhancing customer loyalty by incorporating Islamic values and utilizing relevant media platforms.